PENGARUH HASIL BELAJAR MATA KULIAH MANAJEMEN USAHA RESTORAN TERHADAP MINAT MENJADI ENTREPRENUER MAHASISWA PROGRAM STUDI SENI KULINER AKS AKK YOGYAKARTA - Cristina, Heppi Marta (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
This study aims to describe between Learning outcomes in restaurant business management courses, entrepreneurial motivation and interest in becoming entrepreneurs in culinary arts study program students. The influence of learning outcomes and entrepreneurial motivation on interest in becoming entrepreneurs. This study was conducted on culinary arts study program students with a total of 49 students as respondents. The sampling technique used total sampling, Data collection was carried out using interview techniques, questionnaires and the learning outcomes obtained changed values. Data analysis techniques Scale and Linear Regression The study showed that learning outcomes and interest in becoming entrepreneurs were very high, learning outcomes had a positive and significant effect on interest in becoming entrepreneurs, and significant interest in becoming entrepreneurs, learning outcomes had a significant positive effect on interest in becoming entrepreneurs